EFEK SUPLEMENTASI BERBAGAI AKSELERATOR TERHADAP KUALITAS NUTRISI SILASE LIMBAH TANAMAN SINGKONG - Siti Unayah; Syahrio Tantalo; Liman . (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The purpose of this observation was to know the effect of suplementation lactic acid bacteria inoculum, flour cassava, and the combination between lactic acid bacteria inoculum and flour cassava to  pH value, NH3, and silage nutritional quality of waste cassava plant.  This observation used Complately Randomized Design (CRD) with 4 treatments and 3 repetitions.  The treatment consists of P0: silage of waste cassava plant without suplementation, P1: silage of waste cassava plant with 30 ml lactic acid bacteria inoculum suplementation, P2: silage of waste cassava plant with 5%  flour cassava suplementation, dan P3: silage of waste cassava plant with combination between lactic acid bacteria inoculum and flour cassava suplementation.  The result of this observation showed that significant effect (P<0,01) to pH value, NH3, the levels of dry matter, and crude fiber silage of waste cassava plant, besides the treatment gave significant effect (P<0,05) to the ash content.  The levels of ether extract, crude protein content, and Nitrogen Free Extract (NFE) had not significant affected (P>0,05).